2010
DOI: 10.4321/s1130-01082010000500004
|View full text |Cite
|
Sign up to set email alerts
|

The importance of ultrasound findings in the study of anal pain

Abstract: Objective: endoanal ultrasonography can detect organic causes of anal pain without pathology on physical examination. The aim of this study is to evaluate the importance of endoanal ultrasonography in the diagnosis and therapeutic management of idiopathic and functional anal pain. Material and methods: retrospective study, between 15 March 2005 and 15 June 2008, of all patients with proctalgia and normal examination or with alterations not responsible for anal pain at proctologic exam that have undergone an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…12 In 2010, another study identified specific organic causes of disease in 49% of cases. 13 The difficulties in diagnosing intersphincteric sepsis are well documented, thanks to the absence of external clinical signs such as swelling, induration or perianal hyperemia. 14 Thus, an early diagnosis and effective treatment offer better postoperative functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…12 In 2010, another study identified specific organic causes of disease in 49% of cases. 13 The difficulties in diagnosing intersphincteric sepsis are well documented, thanks to the absence of external clinical signs such as swelling, induration or perianal hyperemia. 14 Thus, an early diagnosis and effective treatment offer better postoperative functional outcomes.…”
Section: Discussionmentioning
confidence: 99%